Caffeine as a Green Corrosion Inhibitor for Carbon Steel in Corrosive Media - Sowad, Rabea Saleh Rabea (Universiti Teknologi PETRONAS, 2016)
In this report, the corrosion inhibition of carbon steel in acidic media is done using caffeine as green inhibitor in hydrochloric acid. The inhibition efficiency of the green corrosion inhibitor was performed using weight loss measurement, Tafel plot and linear polarization resistance method. Weight loss measurement is conducted in samples containing different concentrations of caffeine 0%, 1%, 1.5%, 2%, 2.5%, 3%. The weight loss measurement is done to measure the mass change in the carbon steel coupons in corrosive solution after an interval of 3 days for a month. The inhibition efficiency performance of the 3% solution has reached 67%. It was obvious that with increasing the concentration of the inhibitor, the weight loss is reduced. The second part of this study was investigating the inhibiting influence using Tafel plot, Linear Polarization Resistance (LPR), and Electrochemical Impedance Spectroscopy (EIS). The results have shown great inhibition efficiency performance of the caffeine inhibitor in the corrosive media.